Impact of the 2009 Attica Wild Fires on the Air Quality in Urban Athens - Amiridis, Vassilis; Zerefos, Christos S.; Kazadzis, S.; Gerasopoulos, Evangelos; Eleftheratos, Kostas; Vrekoussis, Mihalis; Stohl, Andreas; Mamouri, Rodanthi-Elisavet; Kokkalis, Panagiotis; Papayannis, Alexandros D.; Eleftheriadis, Konstantinos; Diapouli, Evangelia; et al. (My University, 2012)
At the end of August 2009, wild fires ravaged the north-eastern fringes of Athens destroying invaluable forest wealth of the Greek capital. In this work, the impact of these fires on the air quality of Athens and surface radiation levels is examined. Satellite imagery, smoke dispersion modeling and meteorological data confirm the advection of smoke under cloud-free conditions over the city of Athens. Lidar measurements showed that the smoke plume dispersed in the free troposphere and lofted over the city reaching heights between 2 and 4 km. Ground-based sunphotometric measurements showed extreme aerosol optical depth, reaching nearly 6 in the UV wavelength range, accompanied by a reduction up to 70% of solar irradiance at ground. The intensive aerosol optical properties, namely the Ångström exponent, the lidar ratio, and the single scattering albedo, showed typical values for highly absorbing fresh smoke particles. In-situ air quality measurements revealed the impact of the smoke plume down to the surface with a slight delay on both the particulate and gaseous phase. Surface aerosols increase was encountered mainly in the fine mode with prominent elevation of OC and EC levels. Photochemical processes, studied via NOx titration of O3, were also shown to be different compared to typical urban photochemistry.
Keywords: Aerosol; Biomass burning; Photochemistry; Pollution; Radiation